Ligações químicas em complexos de Ni e Cu com geometrias de coordenação distorcidas e densidade eletrônica experimental de [Cu(2,2'-bipiridina)2N03]N03 - Nahum Ramirez Pineda (2017)
Six complexes of type [ML2(OXO)] Y were synthesized: (I) [Ni(2, 2´-Bipiridina)2Ac]BF4, (II) [Ni(1, 10-Fenantrolina)2Ac]BF4, (III) [Ni(6,6-Dimetil-2,2-dipyridy)2Ac]BF4, (IV) [Cu(3,4,7,8-Tetrametil-1,10-Fenantrolina)2Ac]BF4, (V) [Cu(6,6-Dimetil-2,2-dipiridil)2]BF4 e (VI) [Cu(2,2´-Bipiridina)2NO3]NO3. The structures of all the complexes were determined by single crystal X-ray diffraction. The complex I crystallizes in the P2/c spatial group, the complexes II and IV crystallize in the P21/c group, III e VI in P21/n spatial group and V crystallizes in the P21/a group. Different distortions of the regular coordination geometries are determined for this type of compounds. The crystals are stabilized from different weak hydrogen interactions, which were determined by structural study and checked by analysis of the Hirshfeld surfaces of each compound. For the complex VI, the electron density deformation refinement was performed, obtaining chemically coherent results, which were interpreted from the Quantum Theory of Atoms in Molecules, Obtaining clear evidence of the metal-ligand binding mechanism and distortion of Jahn-Teller type of the complex.